First Report of Phytoplasmas Associated with Strawberry Proliferationand Tall Fleabane Witches’ broom Diseases in West Java, Indonesia: Laporan Pertama Fitoplasma Berasosiasi dengan Penyakit Proliferasi Stroberidan Sapu Jalantir di Jawa Barat, Indonesia - Sholihin, Noor; Mutaqin, Kikin Hamzah; Giyanto (Jurnal Fitopatologi Indonesia, 2026)
Phytoplasmas are bacteria from the class Mollicutes that have been widely reported to be associated with diseases in hundreds of plant species across various countries. In Indonesia, infection of phytoplasmas have been reported from more than eight different plant families. This study aimed to confirm the association of phytoplasmas with strawberry plants showing proliferation symptoms and a wild plant exhibiting witches’ broom symptoms in West Java, using nested-PCR with two primer pairs designed from the 16S–23S rRNA gene region of phytoplasmas. Wild plants were identified both morphologically and molecularly based on the ITS region of the ribosomal RNA gene. Symptoms in strawberry (Fragaria ananassa) include shoot proliferation, phyllody, and dwarf fruits, while the wild plant exhibited witches’ brooms symptoms. The wild plant, commonly known as tall fleabane (Jalantir, in Bahasa Indonesia), was successfully identified as Conyza sumatrensis based on morphological characteristics and nucleotide sequence analysis of PCR amplicons using universal primers ITS1/ITS4. Initial PCR amplification using a primer pair P1/P7 for phytoplasmas from both strawberries and tall fleabane produced a positive DNA band of approximately 1800 bp with inconsistent band intensities. Further amplification using nested-PCR with a primer pair R16F2n/R16R2 yielded a stronger DNA band of approximately 1250 bp. The nested-PCR results confirmed that phytoplasmas are associated with both plants. This study represents the first report of phytoplasma association with strawberries (Rosaceae) and tall fleabane (Asteraceae) in Indonesia.